2023
DOI: 10.1177/20552076231179028
|View full text |Cite
|
Sign up to set email alerts
|

Training for virtual care: What do the experts think?

Abstract: Introduction Virtual care has expanded during COVID-19 and enabled continued access to healthcare services. As with the introduction of any new technology in healthcare delivery, the preparation of healthcare providers for adopting and using such systems is imperative. The purpose of this qualitative study was to explore experts’ ascribed opinions on healthcare providers’ continuing professional development (CPD) needs in virtual care. Methods Semistructured interviews were conducted with a purposive sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…When health practitioners are both professional and have ethical considerations, health information management skills (C97-C102), and data security and privacy (C103-C107), then healthcare is "guaranteed to have quality of care, sustainable costs, professional liability and respect of patient privacy, and data protection and confidentiality" [27]. Clinical expertise and decision-making (C15-C21) allow "healthcare providers to have the knowledge and ability to determine when virtual care is appropriate" [28]. According to HRRS, health equity in virtual care (C22-C25) and virtual health leadership and management (C26-C34) competencies will help health practitioners understand the role of virtual healthcare and aid in meeting the needs of marginalized communities [29].…”
Section: Discussionmentioning
confidence: 99%
“…When health practitioners are both professional and have ethical considerations, health information management skills (C97-C102), and data security and privacy (C103-C107), then healthcare is "guaranteed to have quality of care, sustainable costs, professional liability and respect of patient privacy, and data protection and confidentiality" [27]. Clinical expertise and decision-making (C15-C21) allow "healthcare providers to have the knowledge and ability to determine when virtual care is appropriate" [28]. According to HRRS, health equity in virtual care (C22-C25) and virtual health leadership and management (C26-C34) competencies will help health practitioners understand the role of virtual healthcare and aid in meeting the needs of marginalized communities [29].…”
Section: Discussionmentioning
confidence: 99%
“…The Canadian Institute for Health Information (CIHI) reported that between March to September 2020, the percentage of patients availing of virtual care services increased from 6% to 56% [1]. Virtual care refers to the delivery of healthcare services digitally or at a distance using Information and Communications Technology [2,3,4]. During COVID-19 a variety of virtual care types were used with synchronous and asynchronous appointments being the most common [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual care refers to the delivery of healthcare services digitally or at a distance using Information and Communications Technology [2,3,4]. During COVID-19 a variety of virtual care types were used with synchronous and asynchronous appointments being the most common [3,4]. Synchronous virtual care refers to communication between healthcare provider and patient that occurs in real time and can include use of telephone and/or videoconferencing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations